Influence of Processing on the Physical Stability of Multiple Emulsions Containing a Green Solvent. Issue 6 (19th February 2016) - García, María Carmen; Muñoz, José; Alfaro, María Carmen; Franco, José María
Abstract: The influence of the emulsification process on the microstructure and physical stability of model water‐in‐oil‐in‐water (W/O/W) emulsions formulated with a green solvent and a mixture of amphiphilic copolymers as emulsifiers was investigated. Emulsions were prepared by applying a homogenization step with a rotor‐stator device followed by high‐pressure homogenization. Viscous flow tests, transmitted light optical microscopy, globule size distribution (GSD), and multiple light scattering (MLS) measurements were carried out. The GSDs obtained were the result of a recoalescence due to overprocessing and the coalescence of inner droplets with the outer water phase. MLS detected a main destabilization mechanism by creaming. The passing of the emulsion through a high‐pressure homogenizer (HPH) significantly delayed the creaming process. Abstract : Water‐in‐oil‐in‐water (W/O/W) emulsions still suffer from relatively short stability periods. The impact of the emulsification process on microstructure and physical stability of model W/O/W emulsions formulated with a green solvent and a mixture of amphiphilic copolymers as emulsifiers was examined. Multiple pre‐emulsions were obtained in one homogenization step.